Entre a Escola e a Religião: Desafios para as crianças de Candomblé em Juazeiro do Norte. - Sousa, Kássia Mota de (2010)
This work has as thematic the relation between the child who attends candomblé and school in Juazeiro do Norte, Ceará, Brazil. This research searched to understand the meanings and feelings that these children construct on their pertaining to school experiences. We adopt as research methodologies individual interviews and the participant research. Recognizing the importance of children’s performance in academic research, we opt to knowing, hearing and following five children from candomblé at Terreiro Ilê Axé Gitofalogi, in Juazeiro do Norte, in order to get acquainted with their school experiences. Besides listening to the children, we also interviewed some adults of the community as well as teachers and coordinators, and made comments in the schools where the children studied. Listening to the children, the observation of their reality and the interviews with the religious and school communities which the children attended had demonstrated that children from candomblé, for its religious belonging, are victims of many kinds of prejudice and discrimination. We perceive that religious intolerance against candomblé and religions of African matrix, in general, is a way of reproducing the ideology of racism. We went through a reflection on the juazeirense school reality through the law 10,639/03 and discussed the Religious Teaching and the presence of catholic signs of faith into school environments. Through the analysis of the education experienced by children in Juazeiro, called erês, it was possible to conclude that: children from candomblé are victims of racism in their schools, no matter these schools are public or private. Their aggressors can be teachers, pupils, pedagogical materials and educational practices as well. We also conclude that religious education promoted by the Secretary of Education of Ceará, applied in the city of Juazeiro, if not analyzed critically can constitute as one more place for the practice of multiple discriminations and religious intolerances, when promoting catholicism in detriment of many other religious beliefs to which the children/students keep their identity and belonging.